Arguing Islamophobia during COVID-19 Outbreaks: A Consideration Using Khuṣūṣ Al-Balwᾱ - Bakry, Muammar; Syatar, Abdul; Haq, Islamul; Mundzir, Chaerul; Arif, Muhammad; Amiruddin, Muhammad Majdy (International Journal of Criminology and Sociology, 2021)
The threat of Islamophobia continues to surface. The latest is related to COVID-19. Islam considered as the source of the virus suddenly went viral, even with the hashtag #coronajihad. The implementation of religious rituals by ignoring social distance by certain groups can be one of the triggers besides propaganda and conspiracy from anti-Islam. This article aims to provide an argument against Islamophobia with consideration of Khusus Al Balwa. The approach used is a combination of normative and empirical facts amid the heterogeneity of Muslims during the pandemic. An interesting finding from this research shows that khusus al-balwa is a concept that Muslims need amid co-19 hegemony, especially in terms of providing a complex understanding to present a calming Islam rather than a threat. In reality, khusus al-balwa happened a lot amid the pluralism of Muslims to prevent the outbreak of Islamophobia amid co-19 issues. Consideration of khusus al balwa contribute to prevent the negative stigma that could harass verbally and physically to the muslem. In fact, the special concept of al-balwa has not been much studied by observers of Islamic law which is covered because of the ’fame’ of ‘umum al-balwa. Khusus al-balwa has not been fully taken into consideration by the Mufti, both individuals, and institutions in bringing forth fatwa products.